(3GdMe``GjI GdLf``GFjI dM````QjI GdJYH``jQ Y```f Gd````QCj (B/s - (3CSGeI YHO Gddg GdSYjO eMeO Ydj GdLfOjs; (3CSGeI MSfjf YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3Cf MQjI GdJYHjQ Yf GdQCj, ef Cge GdMbhb hGdMQjGJ GdJj YQagG GdEfSGf, hfUJ YdjgG GdJTQjYGJ hGdOSGJjQ, hCbQJgG GdeYGgOGJ hGdehGKjb, hbO fGdJ GgJeGe GdHGMKhf hGdabgGA hQLGd GdbGfhf hZjQge ef GdegJejf HMbhb hMQjGJ GdEfSGf(B. (3hMQjI GdJYHjQ Yf GdQCj TQW hLhO dZjQgG ef GdMbhb hGdMQjGJ, chfgG eJfaS Mbhb hMQjGJ GdEfSGf, hdSGfgG GdPj jJMOK HGdfjGHI YfgG, hgj GdOdjd GdedehS Ydi JeJY GdCaQGO HMbhbge hMQjGJge GdeNJdaI, agj GdUhJ GdfGWb, hGdaYd GdeDOj, hGdETGQI GdedgeI(B. (3hJfHKb efgG MReI ef GdMbhb hGdMQjGJ GdCNQi PGJ GdUdI cMQjI GdUMGaI, hMQjI GdEYdGe hGdfTQ, hMQjI JOGhd GdeYdheGJ, hMQjI GdEHOGY, hGdMb aj GdJLeY (B((3GdJXGgQ hGdGYJUGe (B... (3GdN(B)(3, hZjQgG GdJj JLO CSGSgG aj MQjI GdJYHjQ Yf GdQCj(B. (3hJcef eTcdI OQGSJfG aj Cf MQjI GdJYHjQ Yf GdQCj QZe GdGYJQGa HgG, EdG CfgG eLQOI ef Cj MeGjI LfGFjI, hbO CXgQJ GdYOjO GdCMOGK aj GdBhfI GdCNjQI eOj GdbUhQ aj JfXje hcaGdI Mb GdCaQGO aj GdJYHjQ Yf BQGFge, dGSjeG aj Xd GNJaGA GdMeGjI GdLfGFjI MbjbjI deeGQSI gPg GdMQjI, eeG Sgd GdGYJOGA Ydjge, hCOj Edi EadGJ GdcKjQ ef GdYbGH GdPj jSJMbg, fJjLI ZjGH GdLRGA GdLfGFj GdQGOY, dPG abO hLHJ GdMeGjI GdLfGFjI GdMbjbjI dgPg GdMQjI(B. (3hGdMeGjI GdLfGFjI df JJCJi EdG HHjGf GdMb aj GdJYHjQ Yf GdQCj hHjGf MOhOg hVhGHWg GdbGfhfjI, Ke EbQGQ GdLQGFe hGdYbhHGJ GdefGSHI dJLQje GdGYJOGA Ydjg, JfajPkG deHOC JLQje GdGYJOGA Ydi GdMbhb hGdMQjGJ, eY hVY GdbjhO hGdVeGfGJ deeGQSI gPg GdMQjI(B. (3dPG, fSYj ef NdGd HMKfG, Edi EjLGO MeGjI LfGFjI eHGTQI hUQjMI hbhjI heJLOOI hab GdJWhQGJ hGdeSJLOGJ GdOhdjI dgPg GdMQjI(B. s
Freedom of expression is one of the most important rights and freedoms recognized by humanity, legislation, constitutions, treaties, and charters have enshrined it. It has garnered the attention of researchers, scholars, legal experts, and others interested in human rights and freedoms. Freedom of expression is a precondition for the existence of other rights and freedoms, as it serves as an outlet for the rights and freedoms of individuals. It is their voice, speaking on their behalf, and it is tangible evidence of individuals enjoying their various rights and freedoms. It is the speaking voice, the action taken, and the inspiring signal. From it, a bundle of other related rights and freedoms arises, such as freedom of the press, freedom of media and publication, freedom of information exchange, freedom of creativity, and the right to assemble (protest and demonstration, and more). All of these rights find their basis in freedom of expression. The problem in our study is that despite the recognition of freedom of expression, it lacks any criminal protection. Recent events have revealed significant shortcomings in regulating and safeguarding the right of individuals to express their opinions, particularly in the absence of genuine criminal protection for the exercise of this freedom. This has made it easier to attack them and has led to many escaping the punishment they deserve due to the absence of a real criminal deterrent. Therefore, true criminal protection for this freedom has become necessary. Criminal protection can only be achieved by specifying the right to express opinions, defining its legal boundaries and regulations, and enacting appropriate crimes and penalties to criminalize attacks on it, by the principle of criminalizing violations of rights and freedoms, while setting restrictions and guarantees for the exercise of this freedom. Therefore, through our research, we seek to establish direct, explicit, strong, and updated criminal protection for this freedom in line with international developments and updates.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B- (3cdjI GdMbhb(B- (3bSe GdbGfhf GdLfGFj, (B2023. s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B397-410.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3MQjI GdJYHjQ Yf GdQCjs; (3GdJXGgQGJ hGdJLeYGJ GdSdejIs; (3GdMbhb hGdMQjGJs; (3GdMeGjI GdLfGFjIs; (3GdehGKjb GdYGdejIs; (3VeGf YOe GdNQhLs; (3GdTQYjI GdLfGFjIs; (3GdCQcGf GdYGeIs; (3eHOC GdeTQhYjIs; (3QbGHI GdHQdeGf s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs